Geoarchaeological map of el Pichao (Tucumán - Argentina): SPECIAL ISSUE ON GEOMORPHOLOGY - Sampietro Vattuone, Maria Marta; Peña Monné, José Luis (Geographicalia, 2024)
The application of geomorphological cartography to geoarchaeological studies is of great interest for the construction of evolutionary models that integrate information on landscape changes with human occupations. The use of drones provides a great advantage for the development of this type of cartography. This map offers detailed information on the geomorphological context of the El Pichao archaeological site, the spatial location of the structures that comprise it, the active morphodynamic processes that affect the site, state of conservation of the complex, and contains detailed information for the conservation of the site. It has been established that the area is at serious risk of heritage loss conditioned by the increase in torrentiality of the system and the processes derived from surface runoff and the action of gravity on the present structures.
Keywords: applied geomorphology; archaeology; drone; UAV; heritage